Comparison of the Character of the Love of the Homeland of Students in Public Elementary Schools - Asrial; Syahrial; Husni Sabil; Dwi Agus Kurniawan; Rahmat Perdana; Sri Muslimatul Husna; Elza Triani (Universitas Pendidikan Ganesha, 2023)
Character education plays an important role in the world of education. One of the character values that has a significant impact in realizing the progress of a nation is the character value of loving the motherland. To be able to foster a sense of caring, loyalty, and always respecting and being proud of the nation and country, students must have the character of loving the motherland. This study aims to compare the character of love for the motherland from the use of the Turun Baumo e-module. The research method used is quantitative research with a comparative design. The sample in this study were 144 students who were taken using the cluster random sampling technique. The research instrument used in this study was a questionnaire about the character of love for the motherland. The data analysis technique used is descriptive statistics and inferential statistics. The results of the t test show that there is a significant difference between students' love for the character of the homeland from the use of the Baumo Derivatives e-module in four elementary schools. So it can be concluded that there is a significant difference between the love of the country character of students and the use of the down baumo e-module. Researchers suggest that further research can be carried out on research on the variable character of patriotism based on class and gender.